Pengaruh Intellectual Capital Disclosure dan Corporate Governance Terhadap Tingkat Uderpricing Pada First Day Listing Date - Adinda Putri Ariyana (Yayasan Literasi Ilmiah Indonesia, 2022)
This study aims to determine the effect of intellectual capital disclosure and corporate governance on underpricing on the first day listing date. The population in this study is the financial statements of companies conducting IPO listed on the Indonesia Stock Exchange (IDX) in 2016-2019 which are downloaded through www.idx.co.id, eith a sample of 35 companies that meet the criteria in this study. This research method uses quantitative and secondary methods, sampling by purposive samplin. Analysis pf the data used in this study using IBM SPSS version 20. The results of this study provide evidence that Intellectual Capital Disclosure, Independence of the Board of Commissioners, Managerial Ownership and Institusional Ownership have a negative influence on underpricing.